Predictive Factors for Hamstring Graft Diameter in Anterior Cruciate Ligament Reconstruction - Thanomsingh, Pachin (Journal of Southeast Asian Orthopaedics, 2025)
Purpose: Hamstring graft diameter is a critical factor in anterior cruciate ligament reconstruction (ACLR), with grafts ≥ 8 mm associated with high failure rates. The accurate prediction of graft size before surgery is particularly important in populations with smaller body frames, such as Asian populations. We aimed to identify the anthropometric and magnetic resonance imaging (MRI) -based predictors of hamstring graft diameters ≥ 8 mm in patients undergoing ACLR. Methods: A retrospective cohort study was conducted in 210 patients (169 men, 41 women) who underwent single-bundle ACLR with quadrupled hamstring autografts at Maharat Nakhon Ratchasima Hospital between 2017 and 2023. Anthropometric data were collected; preoperative MRI measurements of the semitendinosus and gracilis tendons were performed. Graft diameters were recorded intraoperatively following the MRI assessment. All measurements were performed by a single observer. Logistic regression was used to identify predictive factors; a receiver operating characteristic curve was used to evaluate the diagnostic accuracy of the model. Results: Among the 210 patients, 51 (24.3%) had graft diameters < 8 mm. Those with grafts ≥ 8 mm were predominantly men and had greater height, weight, and MRI-derived tendon dimensions. Multivariate analysis identified the semitendinosus tendon cross-sectional area (CSA-ST) as the sole independent predictor. A CSA-ST ≥ 13.4 mm² predicted graft diameters ≥ 8 mm with 70.4% sensitivity (95% CI, 62.7–77.4%), 80.4% specificity (95% CI, 66.9–90.2%), a positive predictive value of 91.8% (95% CI, 85.4–96.0%), a positive likelihood ratio of 3.6 (95% CI, 2.1–6.3), and an area under the receiver operating characteristic curve of 0.79 (95% CI, 0.69–0.82). Conclusions: The CSA ST measured on preoperative MRI is a reliable predictor of hamstring graft adequacy in ACLR. A threshold of 13.4 mm² can assist in surgical planning and graft selection, particularly in patients with smaller body sizes. These findings underscore the importance of incorporating MRI-based assessments into routine preoperative evaluations.